Design like you give a damn. [2], Building change from the ground up - Architecture for Humanity (Organization). (New York ; London : Abrams, 2012)
With the rise in social demand for recycling programs and sustainable living, this volume documents more than 100 new projects from around the world. It is packed with practical and ingenious design solutions that address the need for basic shelter, housing, education, health care, clean water and renewable energy.
Includes bibliographical references : (p. 326-328).
Keywords: Emergency housing -- Design and construction; Buildings, Temporary -- Design and construction; Disaster victims -- Dwellings; Architecture and society